Clinical Practice Guideline: Improving Nasal Form and Function after Rhinoplasty Executive Summary. (1st February 2017) - Ishii, Lisa E.; Tollefson, Travis T.; Basura, Gregory J.; Rosenfeld, Richard M.; Abramson, Peter J.; Chaiet, Scott R.; Davis, Kara S.; Doghramji, Karl; Farrior, Edward H.; Finestone, Sandra A.; Ishman, Stacey L.; Murphy, Robert X.; et al.
Abstract : Objective: Rhinoplasty, a surgical procedure that alters the shape or appearance of the nose while preserving or enhancing the nasal airway, ranks among the most commonly performed cosmetic procedures in the United States, with >200, 000 procedures reported in 2014. While it is difficult to calculate the exact economic burden incurred by rhinoplasty patients following surgery with or without complications, the average rhinoplasty procedure typically exceeds $4000. The costs incurred due to complications, infections, or revision surgery may include the cost of long‐term antibiotics, hospitalization, or lost revenue from hours/days of missed work. The resultant psychological impact of rhinoplasty can also be significant. Furthermore, the health care burden from psychological pressures of nasal deformities/aesthetic shortcomings, surgical infections, surgical pain, side effects from antibiotics, and nasal packing materials must also be considered for these patients. Prior to this guideline, limited literature existed on standard care considerations for pre‐ and postsurgical management and for standard surgical practice to ensure optimal outcomes for patients undergoing rhinoplasty. The impetus for this guideline is to utilize current evidence‐based medicine practices and data to build unanimity regarding the peri‐ and postoperative strategies to maximize patient safety and to optimize surgical results for patients. Purpose: The primary purpose of this guideline executive summary is to provide evidence‐based recommendations for clinicians who either perform rhinoplasty or are involved in the care of a rhinoplasty candidate, as well as to optimize patient care, promote effective diagnosis and therapy, and reduce harmful or unnecessary variations in care. The target audience is any clinician or individual, in any setting, involved in the management of these patients. The target patient population is all patients aged ≥15 years. The guideline is intended to focus on knowledge gaps, practice variations, and clinical concerns associated with this surgical procedure; it is not intended to be a comprehensive reference for improving nasal form and function after rhinoplasty. Recommendations in this guideline concerning education and counseling to the patient are intended to include the caregiver if the patient is <18 years of age. Action Statements: The Guideline Development Group made the following recommendations : (1) Clinicians should ask all patients seeking rhinoplasty about their motivations for surgery and their expectations for outcomes, should provide feedback on whether those expectations are a realistic goal of surgery, and should document this discussion in the medical record. (2) Clinicians should assess rhinoplasty candidates for comorbid conditions that could modify or contraindicate surgery, including obstructive sleep apnea, body dysmorphic disorder, bleeding disorders, or chronic use of topical vasoconstrictive intranasal drugs. (3) The surgeon, or the surgeon's designee, should evaluate the rhinoplasty candidate for nasal airway obstruction during the preoperative assessment. (4) The surgeon, or the surgeon's designee, should educate rhinoplasty candidates regarding what to expect after surgery, how surgery might affect the ability to breathe through the nose, potential complications of surgery, and the possible need for future nasal surgery. (5) The clinician, or the clinician's designee, should counsel rhinoplasty candidates with documented obstructive sleep apnea about the impact of surgery on nasal airway obstruction and how obstructive sleep apnea might affect perioperative management. (6) The surgeon, or the surgeon's designee, should educate rhinoplasty patients before surgery about strategies to manage discomfort after surgery. (7) Clinicians should document patient satisfaction with their nasal appearance and with their nasal function at a minimum of 12 months after rhinoplasty. The guideline development group made recommendations against certain actions: (1) When a surgeon, or the surgeon's designee, chooses to administer perioperative antibiotics for rhinoplasty, he or she should not routinely prescribe antibiotic therapy for a duration >24 hours after surgery. (2) Surgeons should not routinely place packing in the nasal cavity of rhinoplasty patients (with or without septoplasty) at the conclusion of surgery. The panel group made the following statement an option : (1) The surgeon, or the surgeon's designee, may administer perioperative systemic steroids to the rhinoplasty patient.